A case report of diffuse alveolar hemorrhage: A rare and fatal complication of systemic lupus erythematosus - N Meghana; S Prashanth; K Nagendra; C D Thibbegowda; M R Savitha (Indian Journal of Child Health, 2021)
Diffuse alveolar hemorrhage (DAH) is a rare but potentially catastrophic complication of Systemic lupus Erythematosus (SLE), known to complicate about 2–5% of SLE cases. Here, we describe the case of a 9-year-old girl who presented DAH with at the initial diagnosis of SLE. A high index of suspicion is needed for prompt diagnosis in such cases and they require aggressive management at the initial diagnosis to avoid the associated high mortality.